2009
DOI: 10.1089/neu.2008.0717
|View full text |Cite
|
Sign up to set email alerts
|

A New Rating Scale for Open-Field Evaluation of Behavioral Recovery after Cervical Spinal Cord Injury in Rats

Abstract: The Basso, Beattie, Bresnahan (BBB) locomotor rating scale has proven a reliable tool to evaluate impairments of hindlimb locomotor skills after thoracic spinal cord injury (SCI). With the increasing use of cervical SCI rat models, there is a critical need to develop scoring scales designed to more precisely examine alteration and recovery of forelimb functions. The main goal of the present study was to elaborate and evaluate a new rating scale for open-field testing of the fore- and hindlimb locomotor functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 39 publications
1
44
0
Order By: Relevance
“…The scale by Martinez (2009) has been validated for unilateral cervical surgical injuries at C4 in males. However, because of its cumulative scoring approach, it is possible for the same score to represent different forelimb behaviors, which is potentially confusing for experiments designed to investigate structure function relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale by Martinez (2009) has been validated for unilateral cervical surgical injuries at C4 in males. However, because of its cumulative scoring approach, it is possible for the same score to represent different forelimb behaviors, which is potentially confusing for experiments designed to investigate structure function relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has developed the Forelimb Locomotor Scale (FLS) for use in both surgical and contusive unilateral cervical injury (Cao et al, 2008; Sandrow-Feinberg et al, 2009). Martinez (2009) created a modified BBB scale for use in surgical unilateral cervical injury. Anderson (2009) created the Forelimb Locomotor Assessment Scale (FLAS) for use in a midline contusive cervical injury model.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to our data correlating tissue sparing and behavioral outcome, other groups have quantified this relationship. Martinez and colleagues induced C4 hemisections that encompassed varying degrees of white-and graymatter damage, and described a 20-point scale to evaluate forelimb and hindlimb function in an open field test (Martinez et al, 2009). This group reported that lesions associated with the most gray-and white-matter sparing induced less severe deficits in the open field, and that complete hemisection lesions result in severe forelimb deficits with little functional recovery.…”
Section: Tissue Sparing and Functional Recoverymentioning
confidence: 99%
“…The animal model used in this study was subject to chronic compression at the cervical spinal cord, which principally affected the sensory and motor functions of the forelimbs rather than hindlimbs. 27 Therefore, it may suggest the lower sensitivity of BBB scores in detecting the spinal cord dysfunction initiated by chronic compression.…”
mentioning
confidence: 99%